2016
DOI: 10.1016/j.ceramint.2016.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature sintering and dielectric properties of (Ba0.85Ca0.15)(Ti0.9Zr0.1)O3−xCu2+ ceramics obtained by the sol-gel technique

Abstract: Lead-free Cu 2+-modified (Ba 0.85 Ca 0.15)(Ti 0.9 Zr 0.1)O 3 (BCZT-xCu 2+) piezoelectric ceramics was synthesized by sol-gel method. The effects of Cu 2+ additions on sintering characteristics, the phase structure, microstructure, electrical properties and complex impedance characteristic were investigated systematically. The XRD patterns exhibited a pure perovskite structure without impurity phase in all samples. SEM micrographs, temperature dependence of dielectric constant and polarizationelectric field (P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[14][15][16][17] Moreover, it was reported that BCZT ceramics possess low dielectric loss (tan d) (1-3%), which is encouraging for obtaining high-efficiency energy storage density. 10,[18][19][20][21] BCZT relaxor ferroelectric ceramics have been attracting much attention for energy storage applications and electrocaloric cooling devices owing to their outstanding dielectric and ferroelectric properties. 22,23 Zhan et al 24 achieved an energy storage density of 590 mJ cm À3 and storage efficiency (h) of 72.8% in Ba 0.95 Ca 0.05 Zr 0.30 Ti 0.70 O 3 ceramics at 160 kV cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Moreover, it was reported that BCZT ceramics possess low dielectric loss (tan d) (1-3%), which is encouraging for obtaining high-efficiency energy storage density. 10,[18][19][20][21] BCZT relaxor ferroelectric ceramics have been attracting much attention for energy storage applications and electrocaloric cooling devices owing to their outstanding dielectric and ferroelectric properties. 22,23 Zhan et al 24 achieved an energy storage density of 590 mJ cm À3 and storage efficiency (h) of 72.8% in Ba 0.95 Ca 0.05 Zr 0.30 Ti 0.70 O 3 ceramics at 160 kV cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Normally, semicircles in high-, middle-, and low-frequency regions represent the contributions from the grain interior, grain boundary, and ceramic−electrode interface, respectively. 14,46 As shown, large semicircles at the high-frequency range can be observed for both the CBN and CBNCC-0.015 ceramics, revealing that the grains dominate the conduction process of both ceramics. It should be noted that a small arc at the low-frequency range can be noticed for the pure CBN ceramic, which is related to the electrode polarization.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…So as to find out the detailed reason for the change in resistivity, the Nyquist plots of the CBN and CBNCC-0.015 samples at various temperatures are given in Figures c and d. Normally, semicircles in high-, middle-, and low-frequency regions represent the contributions from the grain interior, grain boundary, and ceramic–electrode interface, respectively. , As shown, large semicircles at the high-frequency range can be observed for both the CBN and CBNCC-0.015 ceramics, revealing that the grains dominate the conduction process of both ceramics. It should be noted that a small arc at the low-frequency range can be noticed for the pure CBN ceramic, which is related to the electrode polarization. , A series model of two parallel (CQR) elements is selected to fit the Nyquist plots.…”
Section: Results and Discussionmentioning
confidence: 90%
“…Such type of behaviour can be attributed to the decrease in grain and grain boundary resistances with increasing temperature (Table 3) as these resistances are related to the diameter of the semicircles. For all samples the grain boundary resistance value is higher compared to grain resistance because the grain boundaries are normally more insulating and capacitive than grains [54]. With the increase in temperature, grain boundary resistance decreases and conductivity increases and can be attributed to the ionisation of oxygen vacancies at high temperatures [55].…”
Section: Temperature-dependent Dielectric Analysismentioning
confidence: 92%